Knowledge Management Diagnosis in Vojvodina Firms by Using Bukowitz and Williams Model - Jokanović, Bojana T; Okanović, Andrea V; Lalić, Bojan (Industrija, 2018)
The main purpose of this paper is to empirically analyse the state of knowledge management (KM) practice in one particular region. In order to access the state of Vojvodina firms regarding the applicability of KM program, the Knowledge Management Diagnostic model was applied. Hypotheses based on the specific integrated set of KM were established and statistically tested on a sample of 190 Vojvodina companies from various industries, government institutions and public enterprises. Survey methodology was used with the aim to gather data about KM practice and other related organizational aspects. Our findings show the extent to which individual steps of KM at the whole sample deviate from the maximum value assigned. This survey provides a foundation for practicing engineering managers to position company and recognize the steps of KM that can be improved in order to achieve strategic value and close the gap between the average and maximum value assigned to each step.
Keywords: Survey; State; Knowledge; Knowledge management